2017
DOI: 10.1177/0974910117747770
|View full text |Cite
|
Sign up to set email alerts
|

How Aging Societies May Affect Global Growth Prospects

Abstract: Over the next few decades, the United Nations (UN) has projected that the world will experience significant demographic shifts due to lower birth rates and longer lifespans. 1 The world's population aged 65 and above will increase from 12 percent today to 16 percent in 2050, doubling the old-age dependency ratio 2 to 25.2. These demographic shifts would have material implications. Population aging and its dynamics will influence a number of economic variables and behavioral responses, particularly economic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The shift of population to an aging society affects world economic and sociology concerns in many aspects. One major concern regarding this shift is the health care of the elders, which has become the priority in many countries (1). Another important factor affecting the health condition of the elders is frailty.…”
Section: Research Articlementioning
confidence: 99%
“…The shift of population to an aging society affects world economic and sociology concerns in many aspects. One major concern regarding this shift is the health care of the elders, which has become the priority in many countries (1). Another important factor affecting the health condition of the elders is frailty.…”
Section: Research Articlementioning
confidence: 99%
“…Clearly, the influence of aging is widespread and might be inestimable. As for the specific effects of an aging population structure to a society, studies showed that a fall in productivity and consumption should be a major one in economic prospect, while pension pressures should not be neglected, either [3][4][5]. Moreover, Yoshino and Taghizadeh-Hesary claimed that aging of population could be a structural problem causing recession [6].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid growth of the ageing population requires immediate government concern. An ageing population is believed to be an economic burden through an increasing dependency ratio and decreasing saving rates (Bloom et al , 2015), declining labour supply (Bloom et al , 2015; Otsu and Shibayama, 2016; Loser et al , 2017; Hsu et al , 2018), and increasing expenditure caused by pension schemes, social security and health services (Bloom et al , 2015; Otsu and Shibayama, 2016; Hazra et al , 2018). Indonesia's recent policy response to these ageing issues has been positively and unquestioningly accepted by most Indonesians.…”
Section: Introductionmentioning
confidence: 99%